2016
DOI: 10.1038/gim.2016.47
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic incidental findings in 308 families: The NIH Undiagnosed Diseases Program experience

Abstract: PURPOSEUsing SNP chip and exome sequence data from individuals participating in the NIH Undiagnosed Diseases Program (UDP), we evaluated the number and therapeutic informativeness of incidental pharmacogenetic variants.METHODSPharmacogenomics Knowledgebase (PharmGKB) annotated sequence variants were identified in 1,101 individuals. Medication records of participants were used to identify individuals prescribed medications for which a genetic variant might alter efficacy.RESULTS395 sequence variants, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…A recent study from the NIH Undiagnosed Diseases Program (Lee et al. ) also established that PGx results were informative for guiding therapy in their cohort of 308 families. Lee and colleagues evaluated single nucleotide changes that have been reported to impact drug efficacy based on Pharmacogenomics Knowledgebase (PharmGKB).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from the NIH Undiagnosed Diseases Program (Lee et al. ) also established that PGx results were informative for guiding therapy in their cohort of 308 families. Lee and colleagues evaluated single nucleotide changes that have been reported to impact drug efficacy based on Pharmacogenomics Knowledgebase (PharmGKB).…”
Section: Discussionmentioning
confidence: 99%
“…If we were to pursue PGx testing based on individual medication usage and according to the current actionable genedrug pairs for drug metabolizing genes used at Mayo Clinic (Cook et al 2015), 43 patients would be tested for CYP3A4/5, 35 for CYP2C19, 22 for CYP2D6, 8 for CYP1A2 (MIM:124060), and 9 for CYP2C9. A recent study from the NIH Undiagnosed Diseases Program (Lee et al 2016) also established that PGx results were informative for guiding therapy in their cohort of 308 families. Lee and colleagues evaluated single nucleotide changes that have been reported to impact drug efficacy based on Pharmacogenomics Knowledgebase (PharmGKB).…”
Section: Discussionmentioning
confidence: 99%
“…Over 80% of patients who elected to receive pharmacogenomic findings had at least one actionable result. An investigation of ∌1,100 individuals utilizing data obtained from WES and SNP genotyping found that all individuals had an incidental pharmacogenomic finding; however, the majority of the findings were not clinically significant . Our analysis focused only on gene–drug pairs with evidence‐based guidelines for clinical implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen PharmGKB 1A/1B variants or combinations of variants from the list used at the time of the work were identified in SNP chip sequence data, and 21 PharmGKB 1A/1B variants or combinations of variants were identified in the exome-sequence data using the TruSeq kit (Illumina). Only nine participants had pharmacogenetic IFs/SFs associated with altered efficacy of a prescribed medication, demonstrating that some pharmacogenetic IFs could be potentially useful for guiding therapy, and could be worth reporting [37]. However, another study that interviewed 159 Mayo Clinic clinicians revealed that half of them were uncomfortable with the inclusion of pharmacogenomic data in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our results were limited by the non-determination of all CYP2D6 variants. Another Mayo Clinic study outlined the necessity of using a custom genotyping method to determine all CYP2D6 variants or combinations of variants [37]. If we do not focus on the extreme alleles, 415/700 different patients had at least one listed variant or combination of variants from the PharmGKB 1A category within the CYP2C19 and CYP2C9 gene, relevant to toxicity or variability of pharmacokinetics or pharmacodynamics of different medications (Table 2).…”
Section: Discussionmentioning
confidence: 99%